2000
DOI: 10.1016/s0014-5793(00)01588-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation‐dependent activation of TAK1 mitogen‐activated protein kinase kinase kinase by TAB1

Abstract: TAK1 is a mitogen-activated protein kinase kinase kinase (MAP3K) that is involved in the c-Jun N-terminal kinase/ p38 MAPKs and NF-U UB signaling pathways. Here, we characterized the molecular mechanisms of TAK1 activation by its specific activator TAB1. Autophosphorylation of two threonine residues in the activation loop of TAK1 was necessary for TAK1 activation. Association with TAK1 and induction of TAK1 autophosphorylation required the C-terminal 24 amino acids of TAB1, but full TAK1 activation required ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 19 publications
8
130
0
1
Order By: Relevance
“…However, some studies have shown that the phosphorylation of these sites is insufficient for TAK1 activation (14,15). Consistent with this notion, our recent investigation with PP1 implied that the phosphorylation of TAK1 Ser-412 is important for TAK1 activation and function (30).…”
Section: The Phosphorylation Of Tak1 Ser-412 Is Essential For Tlrsupporting
confidence: 77%
See 1 more Smart Citation
“…However, some studies have shown that the phosphorylation of these sites is insufficient for TAK1 activation (14,15). Consistent with this notion, our recent investigation with PP1 implied that the phosphorylation of TAK1 Ser-412 is important for TAK1 activation and function (30).…”
Section: The Phosphorylation Of Tak1 Ser-412 Is Essential For Tlrsupporting
confidence: 77%
“…In particular, the phosphorylation of residues Thr-184 and Thr-187 located at the TAK1 kinase domain is required for TAK1 kinase activity (10,11). However, a few researchers have suggested that the phosphorylation of TAK1 Thr-187 is insufficient for its activation (12)(13)(14)(15). Thus, additional post-transla-tional modifications are needed.…”
Section: Tgf-␤-activated Kinase 1 (Tak1) Is a Key Kinase In Mediatingmentioning
confidence: 99%
“…5C). We also noted that total TAK1 expression was reduced by TAB1 siRNA, but not by control siRNA, perhaps because TAB1 exists in a 1:1 stoichiometric complex with TAK1 (68) and that activation has a correlation with its stability (29). TAB1 siRNA blocked TGF-␤1-induced TAK1 phosphorylation at Thr-187 but did not alter TGF-␤1-induced Smad2/3 phosphorylation.…”
Section: Tab1 Mediates Tgf-␤1-induced Tak1mentioning
confidence: 67%
“…Proinflammatory cytokines, such as TNF-α and interleukin 1 (IL-1), activate downstream signals in a manner mediated by TGF-β-activated kinase I (TAK1), also known as mitogen-activated protein kinase kinase kinase 7 (Sakurai et al 2000;Wang et al 2001). A recent study showed that O-GlcNAcylation of TAK1-binding protein (TAB1) modulates TAK1-mediated cytokine release when induced by IL-1 and osmotic stress (Pathak et al 2012).…”
Section: Inflammationmentioning
confidence: 99%